Gaya Kepemimpinan Kepala Sekolah Terhadap Guru Training Dengan Guru Tetap - Zahara Salma (Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2025)
This study aims to describe how school principals lead in managing teacher training and permanent teachers at MTs Hifzil Quran Yayasan Islamic Centre North Sumatra. This study uses a descriptive qualitative method by collecting data through in-depth interviews. The results of the study show that school principals apply a democratic leadership style and still follow the applicable rules, both from the foundation and the ministry. This style gives teachers the freedom to work, but still within the agreed limits. Teachers are still given more room to innovate in learning, while training teachers receive more structured guidance. In addition, important decision-making and salary management are in the hands of the foundation, so there are no conflicts related to the welfare of teachers. This research shows that targeted democratic leadership can create a stable, collaborative work environment and encourage improvement in the quality of learning.